Samoan migrants' perspectives on diabetes: A qualitative study. (21st April 2019) - Shahab, Yasin; Alofivae‐Doorbinnia, Olataga; Reath, Jennifer; MacMillan, Freya; Simmons, David; McBride, Kate; Abbott, Penelope
Abstract: Issue addressed: The Samoan community in Australia has one of the highest rates of diabetes in Australia. We explored the experiences and perceptions of Samoan patients living with diabetes and their family members. Methods: Semi‐structured interviews were conducted with adults from a Samoan background living in Australia who had diabetes and their family members. Participants were recruited from a single general practice with a high proportion of Pacific Islander patients, through self‐response to waiting room flyers. Inductive thematic analysis was conducted using a constructivist‐grounded theory approach. This qualitative project was part of the developmental phase of a larger project aiming to promote healthy lifestyles and decrease diabetes in the Samoan community in Sydney, Australia. Results: Twenty participants, aged 36–67 years, were interviewed. The majority was men (n = 13) and all were migrants to Australia. Participants reported a range of barriers to early detection and self‐management of diabetes, including dietary practices common within their culture and the role of church and religion. They identified that pride in their heritage and role within families could be a barrier to care but also provided an opportunity for health promotion. Conclusions: The cultural factors which influence the risk and management of diabetes in the Samoan community in Australia can be the barriers to health change but also provide opportunities for culturally targeted diabetes education and health promotion. So what?: These findings will inform the development of approaches for the prevention and management of diabetes within the Samoan‐Australian community. These include health‐promotion initiatives which take into account the role of cultural dietary practices, diabetes stigma, cultural pride and working with churches.